Physiotherapy Management Of Lateral Medullary Infarct And Transverse Sigmoid Sinus Dural Arteriovenous Fistula - M, Faheema.; A, Rajarajeswari. (Journal of Neonatal Surgery, 2025)
Neurological disorders characterised by complex pathophysiology such as lateral medullary infarct (LMI), dural arteriovenous fistula (DAVF), and cerebral venous sinus thrombosis (CVST) compel thorough rehabilitation. To tackle the particular difficulties exhibited by these illnesses, physical therapists are essential. Because CVST typically presents itself with hemiparesis, seizures, and visual abnormalities, hence exercise intensity and safety must be carefully considered. DAVF may result in venous congestion, leading to motor and cognitive impairments, that can be rectified through targeted exercises and compensatory strategies. LMI, which can manifest by dysphagia, hoarseness, and ataxia, requires a multidisciplinary approach, including physical therapy interventions focused on balance, mobility, and functional activities. By focusing the value of customized evaluation, goal-setting, and evidence-based therapies, this case report seeks to shed light on the physical therapy management of CVST, DAVF, and LMI in a patient. Physical therapists can maximize functional outcomes, improve quality of life, and facilitate effective community reintegration by addressing the unique rehabilitation requirements of these disorders.